Impact of Sustainability Attributes of Menu Labels on Restaurant Green Image and Customer Attitudes - Jo, Jangwoo; Joung, Hyun-Woo; Taylor, James Joseph (Journal of Marketing Development and Competitiveness, 2023)
This study investigated the impact of restaurant sustainability menu labels on restaurant green image and customer attitude by comparing three restaurant sustainability attributes. An analysis of covariance (ANCOVA) and a simple linear regression analysis were employed to test the hypotheses. The results suggested that the three restaurant sustainability attributes, food-focused, environment-focused, and administration-focused attributes, significantly affect restaurant green image. An interaction effect suggests that food-focused sustainability attribute significantly affects restaurant green image only when environment-focused attributes are absent. The findings provide strategies for the efficient allocation and effective execution of limited resources in implementing sustainability activities.